Exposure to a combination of silica nanoparticles and low-dose radiation aggravates lung fibrosis in mice via gut microbiota modulation. Issue 12 (27th November 2020) - Ju, Zhao; Ren, Guofeng; Zhou, Meiling; Jing, Jin; Xiang, Jing; Liu, Xiaodan; Huang, Ruixue; Zhou, Ping-Kun
Abstract : Exposure to silica nanoparticles (SNPs) causes lung fibrosis and threatens human health. Abstract : Exposure to silica nanoparticles (SNPs) causes lung fibrosis and threatens human health. However, it is unknown if low-dose radiation (LDR) exposure exacerbates SNP-induced lung dysfunction. Thus, the aim of our study was to determine the combined effect of SNPs and LDR on lung fibrosis and elucidate the potential mechanisms involved. We used SNP-induced A549 cells and mouse models and detected gut microbiota alteration by 16S rDNA amplicon sequencing. Additionally, lung fibrosis-related parameters were also detected using hematoxylin and eosin (H&E) staining, immunofluorescence (IF) staining, qRT-PCR, and western blot analysis. The histopathological and IF staining assays illustrated that co-exposure of mice to SNPs and LDR had a significant deleterious effect on both lung function and lung fibrosis, in comparison to exposure to SNPs or LDR alone. Furthermore, the abundance of Bacteroidetes significantly increased while that of Firmicutes significantly decreased following co-exposure to SNPs and LDR. Mechanistically, the Notch cascade was activated in chronically SNP-exposed mice with lung fibrosis and A549 cells. Additionally, the Notch pathway-associated proteins showed increased expression levels in the lungs following SNP exposure both in vivo and in vitro . Notably, SNP-induced dysbiosis of the gut microbiota promoted lung epithelial damage by triggering the Notch pathway, resulting in SNP-induced lung fibrosis. However, oral administration of probiotics protected the mice from SNP-induced lung injury. Our results strongly indicate that the activation of the gut microbiota-dependent Notch pathway in response to co-exposure to SNPs and LDR results in lung epithelial injury in vivo . Probiotics supplementation is a potential way to protect against SNP- and LDR-induced lung fibrosis.